Penyuluhan Pentingnya Kemandirian Pangan Dan Gizi Seimbang Dalam Rumah Tangga Melalui Pemanfaatan Pekarangan Lahan Kering Di Desa Gumantar Lombok Utara - Bambang Budi Santoso; Jayaputra Jayaputra; I Komang Damarjaya (Universitas Mataram, 2021)
Agricultural land in the Gumantar Village area is dry land with relatively low productivity and diversification of food production, which then causes low income and food availability for farming families, so that it could have an impact on unbalanced food consumption and nutrition for family members and could also threaten household food security. However, on the other hand, the average farmer household has a fairly large yard, but it has not been used optimally. Therefore, counseling was carried out to the community which aims to increase the knowledge and understanding of farmers on the understanding of balanced nutrition and at the same time use the yard around the house in realizing food independence and fulfilling the nutritional needs of the family. The extension activity was carried out in June 2021. This extension activity was considered successful, seen from the enthusiasm and perseverance of the participants in participating in the extension activity and then hoping for follow-up in the practice of using the yard. The farming community of Gumantar Village has high enthusiasm for the realization of the use of the yard as a source of nutritious food.